Leukotrienes and Inflammation –A Review - Lata Kanyal Butola; Archana Dhok; Ranjit Ambad; Deepika Kanyal; Roshan Kumar Jha (Indian Journal of Forensic Medicine & Toxicology, 2021)
Leukotrienes, together with the prostaglandins and other related compounds, are derived from 20 carbon(eicosa) fatty acids that contain double bonds (enoic). Hence this group of substances is called theeicosanoids. The name leukotriene derives from the original discovery of these substances in white bloodcells (polymorphonuclear leucocytes) and the fact that they all have in common 4 double bonds (hence the4 subscript), 3 of which are in a conjugated triene structure. Leukotrienes do not exist preformed in cells.They are formed from the breakdown of arachidonic acid, a polyunsaturated 20 carbon fatty acid. In itsesterified form, arachidonic acid is bound to the phospholipids of the cell membranes. Both immunologicaland non-immunological stimuli can release arachidonic acid from membrane phospholipids by activatingphospholipase A2. The glucocorticosteroid drugs can inhibit phospholipase A2 and thereby decrease theproduction of all the leukotrienes and hence leukotriene-mediated responses. Generally, inflammation leadsto vasodilation, vascular hyperpermeability, increased blood flow and recruitment of leukocytes to inflamedsites. These events cause enhanced production of cytokines, chemokines, chemical mediators and lipidmediators such as LTs and prostaglandins. Acute inflammation occurs over a short time (seconds, minutesand hours). In contrast, chronic inflammation is a long-lasting inflammatory and immune response thatoccurs over months to years and results in diverse diseases including asthma, allergies, atherosclerosis,arthritis, obesity, cancer and other age-related diseases such as AMD. In this review article we aimed tohighlight the evidence that implicates LTs in physiological function and also in disease processes.